Drug exposure: still an excellent biomarker. (December 2009) - Meza-Junco, Judith; Sawyer, Michael B
Relationships between plasma drug concentrations and clinical outcome have been defined for various chemotherapeutic agents, showing that drug exposure may be a marker of toxicity, mainly hematological and gastrointestinal toxicity, as well as efficacy, expressed as tumor response and survival. Biomarkers provide information for guidance in dosing and the minimization of interindividual variation in response. Drug exposure is commonly measured with parameters such as area under the plasma concentration––time curve, steady-state plasma or serum concentrations, peak concentrations and duration above a threshold concentration. In this review, we focus on drugs where pharmacokinetic/pharmacodynamic relationships as well as systemic exposure have been associated to toxicity and/or efficacy in solid and hematological tumors, these include: carboplatin, methotrexate, busulphan, 5-flurouracil, etoposide, anthracyclines, irinotecan, vinorelbine and docetaxel.